RELATIONSHIP BETWEEN PARENTING STYLES AND ACADEMIC PERFORMANCE OF JUNIOR SECONDARY SCHOOL STUDENTS IN NIGER STATE, NIGERIA - Baji, Ibrahim Mohammed; Mohammed, Aisha I. (Sokoto Educational Review, 2018)
This study investigated the influence of parenting styles on academic performance of secondary school students in Niger state, Nigeria. The study employed a correlational design to measure the relationship between parenting styles and academic performance. A sample of 380 junior secondary school students during 2013/2014 academic session was selected from public schools through simple random sampling technique. The research instrument used was Parenting Styles Questionnaire (PSQ) which measured parenting styles across authoritative parenting, authoritarian parenting, and permissive parenting styles. The PSQ was validated through content validity and had a reliability coefficients alpha of .800. The second instrument was academic achievement tests in English language and Mathematics which were developed by subject teachers teaching at the SSS level and their content and construct validity were determined by the inspectors in charge of these specialty areas at the Inspectorate Division, Ministry of Education, Minna. The statistical tools used for analysis of the data include mean, standard deviation, and Pearson Product Moment Correlations. The findings revealed that there were positive correlations between parenting styles and academic performance of JSS students with correlation values expressed as: Authoritative parenting style (r = .154, p< 0.05), authoritarian parenting style (r = .102, p< 0.05), and permissive parenting style (r = .066, p>0.05). Based on the findings of this study, it is recommended that parents should encourage, support and monitor academic activities of children to improve their performance.